2023
DOI: 10.1101/2023.10.30.564726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perilipin membrane-integration determines lipid droplet heterogeneity in differentiating adipocytes

Mario Majchrzak,
Ozren Stojanović,
Dalila Ajjaji
et al.

Abstract: SummaryThe storage of fat within lipid droplets (LDs) of adipocytes is critical for whole-body health. Acute fatty acid uptake by adipocytes leads to the formation of at least two LD-classes marked by distinct members of the perilipin (PLIN) protein-family. How LD-heterogeneity arises is an important yet unresolved cell biological problem. Here, we show that an unconventional integral membrane-segment targets the adipocyte specific LD-surface factor PLIN1 to the endoplasmic reticulum (ER) and binds with high a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…In agreement, a recent preprint shows that PLIN1 can interact with the ER and LDs using hydrophobic segments in its degenerate C‐ter region (Fig. 1), suggesting that PLIN1 targets LDs via the ERTOLD pathway [65].…”
Section: Targeting Of Perilipins To Lds In Cellssupporting
confidence: 76%
See 1 more Smart Citation
“…In agreement, a recent preprint shows that PLIN1 can interact with the ER and LDs using hydrophobic segments in its degenerate C‐ter region (Fig. 1), suggesting that PLIN1 targets LDs via the ERTOLD pathway [65].…”
Section: Targeting Of Perilipins To Lds In Cellssupporting
confidence: 76%
“…The mode of interaction of this region of PLIN1 with LDs has been recently explored by Klemm and coworkers. They show that the first hydrophobic segment mediates high lipid‐binding affinity of PLIN1, possibly acting as a hairpin loop to anchor PLIN1 to the LD surface or the ER bilayer, with an additional contribution of a downstream hydrophobic region [65].…”
Section: Structural and Biochemical Properties Of Perilipinsmentioning
confidence: 99%
“…We investigated the spatial organization of confined LDs with ER and mitochondria to verify this hypothesis. We first examined Plin1 which relocates from the ER to LDs 24,27,31 , and found that LDs labeled by emGFP-Plin1 were juxtaposed to ER structures labeled with mCherry-Sec61 (Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
“…However, when the Cidec-GFP-or GFP-Plin1-positive signals surrounding a LD were completely bleached, the recovery rate of GFP-positive signals was very low, and there was no fluorescence signal recovery even after 5 min, indicating a slow replenishing of Cidec or Plin1 from the ER to the LD surface [41,98]. Some studies have shown that CIDEs and Plin1 are a class of ER-bound proteins, which move from the ER to LDs [43,99,100]. On the contrary, ADRP and Plin5 can rapidly shuttle between LDs and the cytoplasm, rather than just moving on the LD surface [41,98].…”
Section: Molecular Aspects Of Cide Members In Step-wise Ld Fusionmentioning
confidence: 99%